Study of Education Sector Scenario in India: An Analysis of Education Sector in India (Journal of Advances and Scholarly Researches in Allied Education, 2019)
India holds an important place in the world education industry. Presence of private and government universities, as well as well-structured skill development programme, have made India significant position in education sector. This paper reflects study of education sector scenario in India.